Backoff Time Adjustment of Contention Based Request for Fast Uplink WiMAX Video Transmission - -, Fakhrur Razi, Suherman (JITROKOM, 2015)
Abstractâ Bandwidth request and allocation mechanisms manage and satisfy the uplink bandwidth needs of the WiMAX subscriber stations. Bandwidth request losses are handled by a truncated binary exponential backoff (TBEB) algorithm, which is influenced by the changes of traffic rates, uplink frame sizes as well as uplink ratios. Study on existing works shows no method available to adapt those variations. This paper proposes backoff time adjustment to adapt traffic and properties changes. The NS-2 evaluation shows that the proposed method consistently reduced delay for various traffic rates and frame sizes. Delay suppression achieves up to 20.27%, while throughput and packet loss characteristics remain similar.KeywordsâWiMAX, Traffic Rates, Frame SizeAbstractâMetode permintaan dan alokasi bandwidth mengatur kebutuhan bandwidth pelanggan WiMAX. Jika gagal, maka algoritma truncated binary exponential backoff (TBEB) mengatasinya. Kualitasnya dipengaruhi perubahan trafik, ukuran frame dan rasio bandwidth. Riset terdahulu belum ada yang menerapkan parameter tersebut ke dalam TBEB. Artikel ini mengajukan pengaturan waktu TBEB untuk mempercepat transmisi uplink. Evaluasi dengan simulasi NS-2 menunjukkan konsistensi pencapaian metode tersebut. Penekanan Delay mencapai 20.27%, dimana throughput dan packet loss tak jauh berubah.Kata Kunciâ WiMAX, Laju Trafik, Ukuran Frame